Type-2 Diabetes as a Risk Factor for Severe COVID-19 Infection - Norouzi, Mahnaz (Microorganisms, 2021)
The current outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), termed coronavirus disease 2019 (COVID-19), has generated a notable challenge for diabetic patients. Overall, people with diabetes have a higher risk of developing different infectious diseases and demonstrate increased mortality. Type 2 diabetes mellitus (T2DM) is a significant risk factor for COVID-19 progression and its severity, poor prognosis, and increased mortality. How diabetes contributes to COVID-19 severity is unclear; however, it may be correlated with the effects of hyperglycemia on systemic inflammatory responses and immune system dysfunction. Using the envelope spike glycoprotein SARS-CoV-2, COVID-19 binds to angiotensin-converting enzyme 2 (ACE2) receptors, a key protein expressed in metabolic organs and tissues such as pancreatic islets. Therefore, it has been suggested that diabetic patients are more susceptible to severe SARS-CoV-2 infections, as glucose metabolism impairments complicate the pathophysiology of COVID-19 disease in these patients. In this review, we provide insight into the COVID-19 disease complications relevant to diabetes and try to focus on the present data and growing concepts surrounding SARS-CoV-2 infections in T2DM patients.